2002
DOI: 10.1128/mcb.22.3.816-834.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hsp27 as a Negative Regulator of Cytochrome c Release

Abstract: We previously showed that Hsp27 protects against apoptosis through its interaction with cytosolic cytochrome c. We have revisited this protective activity in murine cell lines expressing different levels of Hsp27. We report that Hsp27 also interferes, in a manner dependent on level of expression, with the release of cytochrome c from mitochondria. Moreover, a decreased level of endogenous Hsp27, which sensitized HeLa cells to apoptosis, reduced the delay required for cytochrome c release and procaspase 3 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
338
2
17

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(368 citation statements)
references
References 83 publications
11
338
2
17
Order By: Relevance
“…It has recently been shown that Hsp27 phosphorylation by Akt leads to disruption of the Akt-Hsp27 interaction, and it has been suggested that released Hsp27 may promote independent survival signals (31). It has also been postulated that Hsp27 inhibits apoptosis through inactivation of caspase-3, caspase-9, and inhibition of cytochrome c release (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that Hsp27 phosphorylation by Akt leads to disruption of the Akt-Hsp27 interaction, and it has been suggested that released Hsp27 may promote independent survival signals (31). It has also been postulated that Hsp27 inhibits apoptosis through inactivation of caspase-3, caspase-9, and inhibition of cytochrome c release (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp27 prevents apoptosis by interacting with caspase-3 to modulate its activity, [47][48] by interacting with cytochrome c to prevent procaspase-9 activation, 49 or by regulating Bid intracellular distribution and F actin integrity to block mitochondrial death pathway. 52 In contrast, a-crystallin utilizes a different mechanism to negatively regulate caspase-3 activity. Our recent study shows that aB-crystallin prevents H 2 O 2 -induced apoptosis through interaction with procaspase-3 and partially processed procaspase-3 to prevent caspase-3 activation.…”
Section: Antiapoptotic Mechanisms Of A-crystallinsmentioning
confidence: 99%
“…Its proapoptotic ability can be inhibited by Bcl-2 and Bcl-X L . 38 Another important group of apoptosis regulators are heatshock proteins that include alpha-crystallins (a-crystallins), [39][40][41][42][43][44][45][46] Hsp27, [39][40][47][48][49][50][51][52] Hsp70, [53][54][55][56][57] Hsp90 58 and Hsp60. [59][60] While Hsp60 appears to enhance apoptosis by promoting maturation of procaspase-3, 59,60 the majority of these factors seems to protect cells from induced apoptosis through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-documented antiapoptotic properties of HSP27 exhibited in cell culture (Garrido et al, 1999;Bruey et al, 2000;Paul et al, 2002) have also been shown in vivo in the kainate seizure model, in which HSP27 attenuates caspase 3 induction and reduces apoptotic cell death (Akbar et al, 2003). The formation of HSP27 oligomers necessary for reducing oxidative damage in cellular models has also been shown in cardiac ischemia (Hollander et al, 2004).…”
Section: Introductionmentioning
confidence: 95%